2022
DOI: 10.3389/fsurg.2022.928294
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and prognostic indicators in upper-tract urothelial carcinoma with bone metastasis

Abstract: PurposeWith the gradual increase in the incidence of upper-tract urothelial carcinoma (UTUC), its metastatic disease has attracted much attention. The prognosis of UTUC patients with bone metastasis is worse than that of UTUC patients with other metastases. Therefore, the current study is performed to analyze the clinicopathologic features and survival predictors among UTUC patients with bone metastasis.Patients and methodsWe reviewed the Surveillance, Epidemiology, and End Results (SEER) database to select ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
4
1
Order By: Relevance
“…Liu et al suggested that the prognosis of stage IV metastatic uroepithelial carcinoma depends on the number of metastases from other organs, with no difference in OS compared to other metastatic sites when using bone metastasis as a reference [ 30 ]. Importantly, our findings contrast with those of Zhou et al [ 7 ], who reported that lung metastasis was identified as a risk factor for OS in UTUC patients with BM. This discrepancy could be attributed to the fact that their study did not further stratify cases based on the presence of multiple metastases.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Liu et al suggested that the prognosis of stage IV metastatic uroepithelial carcinoma depends on the number of metastases from other organs, with no difference in OS compared to other metastatic sites when using bone metastasis as a reference [ 30 ]. Importantly, our findings contrast with those of Zhou et al [ 7 ], who reported that lung metastasis was identified as a risk factor for OS in UTUC patients with BM. This discrepancy could be attributed to the fact that their study did not further stratify cases based on the presence of multiple metastases.…”
Section: Discussioncontrasting
confidence: 99%
“…Simultaneous metastases to other sites were common in UTUC patients with BM and significantly reduced their survival rates [ 7 , 29 ]. Liu et al suggested that the prognosis of stage IV metastatic uroepithelial carcinoma depends on the number of metastases from other organs, with no difference in OS compared to other metastatic sites when using bone metastasis as a reference [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patients should understand the long-term prognosis and treatment options available [9]. These patients demand special attention as bone metastasis has a less favorable prognosis as compared to other metastatic sites [10] and also due to the high rate of skeletal-related events like severe spinal instability, intractable pain, and poor life quality, which is a big factor in restricting the application of chemotherapy [2]. Non-operative treatment is advised when tumor involvement has not led to spinal instability, neurological involvement, or intractable pain unresponsive to medical management and includes radiotherapy, chemotherapy, hormonal therapy, and high-dose steroid therapy.…”
Section: Discussionmentioning
confidence: 99%